2021
DOI: 10.1002/plr2.20106
|View full text |Cite
|
Sign up to set email alerts
|

Registration of ‘KS Silverado’ hard white winter wheat

Abstract: ‘KS Silverado’ (Reg. no. CV‐1175, PI 693936) hard white winter wheat (Triticum aestivum L.) was developed at the Agricultural Research Center–Hays, Kansas State University, and released by the Kansas Agricultural Experiment Station in 2019. KS Silverado was selected from a three‐way cross KS05HW122‐5‐2//KS05HW15‐2‐2/KS06HW46‐3 made in 2008 at Hays, KS. The objective of this cross was to develop a hard white winter wheat cultivar that is adapted to Kansas. KS Silverado was selected as an F6–derived line using a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 22 publications
0
4
0
Order By: Relevance
“…Only the results from dryland trials in western Kansas were reported because KS Hamilton was released for dryland production in western Kansas. The seven common checks include three newly released cultivars for this region, KS Dallas, 'KS Silverado' (PI 693936) (Zhang et al, 2021b), and 'KS Western Star' (PI 693935) (Zhang et al, 2021a), and four popular cultivars in this region, Joe, 'SY Monument' (PI 672581), 'T158', and 'WB-Grainfield' (PI 665062). The quality data from six western KIN trials were compared using paired t test function in Microsoft Excel.…”
Section: Core Ideasmentioning
confidence: 99%
“…Only the results from dryland trials in western Kansas were reported because KS Hamilton was released for dryland production in western Kansas. The seven common checks include three newly released cultivars for this region, KS Dallas, 'KS Silverado' (PI 693936) (Zhang et al, 2021b), and 'KS Western Star' (PI 693935) (Zhang et al, 2021a), and four popular cultivars in this region, Joe, 'SY Monument' (PI 672581), 'T158', and 'WB-Grainfield' (PI 665062). The quality data from six western KIN trials were compared using paired t test function in Microsoft Excel.…”
Section: Core Ideasmentioning
confidence: 99%
“…Historically hard wheat ( Triticum aestivum L.) cultivars developed in the Great Plains have tended to be hard red winter wheat, though the market for hard white winter wheat is clearly valuable, and more hard white winter cultivars are becoming available (e.g., ‘Sunshine’, Haley et al., 2017; ‘Matterhorn’, Graybosch et al., 2019; and ‘KS Silverado’, Zhang et al., 2021). As described by Zhang et al.…”
Section: Introductionmentioning
confidence: 99%
“…As described by Zhang et al. (2021), a major limitation to the expansion of hard white wheat is the limited number of grain elevators that accept hard white wheat. Hard red and hard white wheat grains are classified as separate market classes and must be kept segregated in grain elevators to avoid having wheat of mixed classes, which increases elevator costs and potential value risk.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation